Cardiovascular considerations for the athlete with COVID-19 - Weiss, M.; Chung, E. H. (EPLab Digest, 2021)
The cardiovascular effects of COVID-19 infection on athletes and the population at large is a topic of ongoing research and debate. Atrial or ventricular arrhythmias, acute coronary syndrome, thrombosis, cardiogenic shock, myocarditis, and stress-induced cardiomyopathy are some of the known manifestations of COVID-19-related cardiac injury.1 Myocarditis, historically attributed to 3% to 12% of sudden cardiac deaths in athletic populations,2 is one of the most concerning consequences of this novel virus in athletes. In the early stages of the pandemic, sporting activities at every level were cancelled. However, more recently, some professional sports — with intensive testing and isolation protocols — have resumed play, while collegiate, high school, and recreational sports have resumed to varying degrees. In this article, we summarize the current body of literature on the cardiovascular effects of COVID-19 on athletes, as well as expert recommendations on the management of affected patients in this population.